Histological changes during fracture repair with hydroxyapatite fibrillar collagen implants in calves - KUMAR, VINAY; VARSHNEYA, A C; SHARMA, D N; SINGH, MOHINDER (The Indian Journal of Animal Sciences, 2013)
Male calves (18) were subjected to mid- shaft transverse metararsal fractures and divided equally into 2 groups. Group 1 was kept as control whereas in group 2, 3 cm long hydroxyapatite fibnllar collagen implant was unprcgnated in the medullary cavity. The operated limb was immobilized with plaster cast suppotted with aluminum splints. Full thickness bone pieces were collected from the fractured repair site under local analgesia on 30, 60 and 90 days of fracture from the animals of groups 1 and 2 both and subjected to hIstological studies. Use of hydroxyapatite fibrillar collagen implant initiated the osteoid formation at 30 days, osteon formation accompanied with resorption of the implant at 60 days and establishment of Haversian system (compact bone) at 90 days revealing a faster rate of healing with the use of the implant as compared to those of the control animals which showed osteoids even up to 90 days With little lamellar organization.